2019
DOI: 10.1098/rsos.181042
|View full text |Cite
|
Sign up to set email alerts
|

Beetle-bearing coprolites possibly reveal the diet of a Late Triassic dinosauriform

Abstract: Diets of extinct animals can be difficult to analyse if no direct evidence, such as gut contents, is preserved in association with body fossils. Inclusions from coprolites (fossil faeces), however, may also reflect the diet of the host animal and become especially informative if the coprolite producer link can be established. Here we describe, based on propagation phase-contrast synchrotron microtomography (PPC-SRμCT), the contents of five morphologically similar coprolites collected from two fossil-bearing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…Beyond this floristic association, the dicynodont coprolites also preserve diverse arthropod and fungal remains (Perez Loinaze et al ., ) that occur in the aftermath of a major evolutionary radiation that resulted in the establishment of modern insect groups during the Middle Triassic (Misof et al ., ; Van Eldijk et al ., ). It has been recently suggested that insects would have represented the main food item of some early dinosauriforms (Qvarnström et al ., ). The exploitation of this important food resource would have required skeletal adaptations as those observed in Lewisuchus admixtus and that may suggest that this animal had an active predatory behavior, as indicated by a proportionally large head with numerous recurved and serrated teeth, possible good locomotion agility (indicated by a large floccular fossa), and gracile, elongated hindlimbs.…”
Section: Discussionmentioning
confidence: 97%
“…Beyond this floristic association, the dicynodont coprolites also preserve diverse arthropod and fungal remains (Perez Loinaze et al ., ) that occur in the aftermath of a major evolutionary radiation that resulted in the establishment of modern insect groups during the Middle Triassic (Misof et al ., ; Van Eldijk et al ., ). It has been recently suggested that insects would have represented the main food item of some early dinosauriforms (Qvarnström et al ., ). The exploitation of this important food resource would have required skeletal adaptations as those observed in Lewisuchus admixtus and that may suggest that this animal had an active predatory behavior, as indicated by a proportionally large head with numerous recurved and serrated teeth, possible good locomotion agility (indicated by a large floccular fossa), and gracile, elongated hindlimbs.…”
Section: Discussionmentioning
confidence: 97%
“…Following this criterion Asilisaurus would be categorized as a potential piscivore. However, dietary reconstructions of Silesaurus opolensis , another silesaurid possessing similar dentition to Asilisaurus , have been herbivorous or omnivorous based upon dental microwear (Kubo & Kubo, 2014) or insectivorous based upon coprolites (Qvarnström et al, 2019). Thus, in the Manda Beds tooth assemblage, there are two large-bodied carnivores ( Nundasuchus and “ Pallisteria ”), two small-bodied carnivores ( Parringtonia and an undescribed pseudosuchian), and one small-bodied, non-carnivore ( Asilisaurus ).…”
Section: Discussionmentioning
confidence: 99%
“…1) in a marginal marine setting, in order to identify the tracemaker and infer its diet. The specimens were analyzed using scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS) and propagation phase contrast synchrotron microtomography (PPC-SRµCT), a method which has been recently shown to be capable of non-destructively imaging entire coprolite contents of various sorts in three dimensions (Zatoń et al, 2017; Qvarnström et al, 2017; Qvarnström, Ahlberg & Niedźwiedzki, 2019a; Qvarnström et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%